Digitalizacija pri obvladovanju podatkov, procesov in dokumentov v farmacevtskem razvoju generičnih zdravil - Hudovornik, Grega (Farmacevtski vestnik, 2021)
Digitalisation has recently changed the way many industries operate and is increasingly influencing the development of generic medicines in the pharmaceutical industry. The idea of digital transformation in the pharmaceutical industry is very broad and ranges from different ways of capturing and managing data throughout the product life cycle to transformation in terms of increased emphasis on personalised medicine. This article focuses on electronic data management systems, process analytical technology tools and on document management in the registration phase, which are significantly changing the pharmaceutical development in the generic industry.
Keywords: Digitalizacija; Farmacevtska industrija; farmacevtski razvoj; obvladovanje podatkov; procesno analizna tehnologija